2018
DOI: 10.21831/socia.v15i2.22678
|View full text |Cite
|
Sign up to set email alerts
|

Diversitas persepsi masyarakat terhadap pendidikan

Abstract: Persepsi masyarakat tentang sesuatu hal dapat berbeda berdasarkan pengalaman baik yang dialami secara pribadi maupun kolektif. Dalam penelitian ini fokus utama adalah melihat dan mendeskripsikan secara mendalam, beragam persepsi yang ada khususnya pada masyarakat gang Mundu. Jarak yang tidak seberapa jauh dengan Kampus Gedong Unindra dapat menghasilkan beragam persepsi masyarakat mengenai pendidikan. Persepsi tidak hanya sekedar berbentuk opini, melainkan dapat terwujud dalam suatu aktivitas yang didorong oleh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…In addition, previous study revealed that the improvement of learning outcomes becomes one of indication of success evaluation of product (Andrianto & Suyitno, 2021). Moreover, previous study strengthen that internalization of character also contributes to evaluation of product since students try to internalize the character into themselves (Utomo, 2017). However, the different result is found by other studies in which the process evaluation of the previous studies was still ineffective (Dwi et al, 2018;Lawung, 2023).…”
Section: Discussionmentioning
confidence: 71%
“…In addition, previous study revealed that the improvement of learning outcomes becomes one of indication of success evaluation of product (Andrianto & Suyitno, 2021). Moreover, previous study strengthen that internalization of character also contributes to evaluation of product since students try to internalize the character into themselves (Utomo, 2017). However, the different result is found by other studies in which the process evaluation of the previous studies was still ineffective (Dwi et al, 2018;Lawung, 2023).…”
Section: Discussionmentioning
confidence: 71%
“…In this study, the authors used historical research methods (Anggraeni & Setiawan, 2022). According to Louis Gottschalk, the historical method is a process for critically examining and analyzing the records and legacies of events that occurred in the past (Fadli, 2021;Utomo, 2017;Wasino & Hartatik, 2018). The stages of the historical research method are as follows:…”
Section: Methodsmentioning
confidence: 99%
“…(Sugihen, 1996 : 26-28) Pendidikan nasional berfungsi mengembangkan kemampuan dan membentuk watak serta peradaban bangsa yang bermatabat dalam rangka mencerdaskan kehidupan bangsa (UUSPN, 2017 : 86). Fungsi pendidikan di negeri Indonesia adalah untuk mensukseskan pembangunan nasional dalam pengertian luas, karena pendidikan diarahkan kepada terciptanya manusia bermental membangun, yang memiliki keterampilan, berilmu pengetahuan sesuai dengan perkembangan pembangunan Negara serta memiliki akhlak yang luhur dengan kepribadian yang bulat dan harmonis (Abdurahman, 2017;Utomo & Sugiharti, 2018). Dalam hubungan ini pendidikan agama Islam khususnya berfungsi untuk membentuk manusia pembangun, yang memiliki moral yang tinggi dan bertaqwa kepada Allah yang kecuali memiliki kemampuan mengembangkan diri (individualitas), bermasyarakat (sosialitas) serta norma susila menurut agama Islam (Rosyidah, 2008;Sodikin & Maarif, 2021).…”
Section: Diskusiunclassified